2019
DOI: 10.1177/0271678x19876876
|View full text |Cite
|
Sign up to set email alerts
|

The effect of angiopoietin-1 upregulation on the outcome of acute ischaemic stroke in rodent models: A meta-analysis

Abstract: Clinical studies report that low circulating angiopoietin-1 concentration at presentation predicts worse outcomes after ischaemic stroke. Upregulating angiopoietin-1 may therefore have therapeutic benefit for ischaemic stroke. This systematic review assessed whether upregulating angiopoietin-1 improved outcomes in rodent models of ischaemic stroke. Random-effects models quantified the effect of angiopoietin-1 upregulation on stroke severity in terms of the size of cerebral infarction and the extent of blood–br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…The reduction in lesion volume may contribute to improved neurological function in VT‐treated rats compared to control T1DM stroke rats. The neuroprotective effects of Ang1 treatment in non‐DM rodents have been previously demonstrated 7,8,14,48–50 . In non‐DM rats subject to 2 h of transient MCAo stroke, intravascular administration of recombinant Ang1 (1 μg/kg) once every 12 h starting immediately after reperfusion significantly decreases neurological severity score, decreases infarct volume, attenuates BBB leakage, and increases the expression of tight junction proteins in the ischemic brain 49,50 .…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…The reduction in lesion volume may contribute to improved neurological function in VT‐treated rats compared to control T1DM stroke rats. The neuroprotective effects of Ang1 treatment in non‐DM rodents have been previously demonstrated 7,8,14,48–50 . In non‐DM rats subject to 2 h of transient MCAo stroke, intravascular administration of recombinant Ang1 (1 μg/kg) once every 12 h starting immediately after reperfusion significantly decreases neurological severity score, decreases infarct volume, attenuates BBB leakage, and increases the expression of tight junction proteins in the ischemic brain 49,50 .…”
Section: Discussionmentioning
confidence: 85%
“…Ang1 has previously been shown to reduce infarct volume in mice subjected to focal cerebral embolic ischemia 7 . A meta‐analysis study of 11 pre‐clinical stroke studies reported that Ang1 upregulation significantly decreases lesion volume and improves BBB integrity following transient ischemic stroke in rodents 14 . Treatment with Ang1 has also been shown to reduce neuronal cell death by inhibiting the upregulation of pro‐apoptotic factors in vitro 47 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the remodeling phase after myocardial infarction, endothelial-and macrophage-derived ANGPT2 promotes abnormal vascular remodeling and exacerbates inflammation. In contrast, ANGPT1 plays a protective role in preclinical models of vascular injury [37,38] and exerts anti-inflammatory effects [20].…”
Section: Discussionmentioning
confidence: 99%
“…ANGPT2 has been proposed as a prognostic biomarker of adverse cardiovascular events in myocardial infarction [34] and after percutaneous coronary intervention (PCI) [35,36]. In contrast, ANGPT1 plays a protective role in rodent models of vascular injuries [37,38].…”
Section: Introductionmentioning
confidence: 99%